A multi-layer approach of orthogonally fed circularly polarized microstrip array antenna for enhanced gain. Issue 5 (8th March 2019) - Rahman, Muhammad Asad; Nishiyama, Eisuke; Hossain, Md. Azad; Hossain, Quazi Delware; Toyoda, Ichihiko
Abstract: A new circularly polarized microstrip array antenna using the orthogonal feed technique is proposed in this paper. The antenna has a multi-layer structure and a new 3-way power divider employing the both-sided microwave integrated circuit technology is designed to configure the feed network of the array. Circular polarization (CP) is realized by creating a quadrature phase difference between orthogonal feed circuits of the patches. The multi-layer structure gives flexibility to adjust the patch spacing that helps to reduce the sidelobe level of the antenna. It is found that the multi-layer structure exhibits a gain of about 2 dB higher than that of a single layer structure by means of sidelobe reduction. The proposed structure also exhibits good CP performances that are verified by a good agreement of measured and simulated results. Simple and compact structure makes the antenna suitable for various wireless applications.